Innovative Work Practices: A Time to Go Beyond Experimentation (American Journal of Management, 2022)
In the US there have been three major evolutionary steps in the development of organizations after World War II. The first stage is with management as a function, the second is with the command and control organization and the third is decentralization and distinction between policy and operations. The third stage is evolving away from the command-and-control organization to knowledge-based organizations. Organizations implement innovative work practices that create knowledge-based organizations. This paper discusses some of these practices and the issues faced in implementing them. The authors conclude by pointing out that aside from entities such as civil society and unions etc., institutional support and support from public policy bodies is crucial to implementing innovative work systems that create sustainable organizations.
Keywords: management; innovative work practices; quality improvement; high-performance work systems; knowledge-based organizations